PERAN KOMUNIKASI DALAM MODERNISASI DI INDONESIA - Daru Retnowati (Jurnal Dinamika Sosial Ekonomi, 2007)
Modenization is a change in society for each personal creativity along with the change of attitude, behavior and some values to be development. Furthermore, people's awareness of having high quality, the need of basic education and knowledge play a big role toward economic growth. Besides those qualities, communication also has a big role in sosial, economic, politic and culture. Intenractive communication concern with the need of people in rural area will be useful to be implemented some development programs that has been planning. Persuasive communication will influence the farmers to inacrease their crop in Agribusiness and Agoindustry. So import substitution could also be increase. But, to realize these some policies that the farme has to be supported, this process finally will support the modernization.Keywords : Communication, Modernization, social Change